Teaching reading and writing to two students with intellectual disabilities from a computerized teaching program (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This study evaluated the effectiveness of a computerized teaching program in reading and writing skills to two students with intellectual disabilities. The teaching program was applied as a complementary resource. Participants were two students with intellectual disabilities, aged between 6 and 12 years, enrolled in the 3rd. and 6th. primary school. After a overall assessment of target skills, participants were exposed to teaching sessions, with matching to sample and constructed-response matching to sample procedures. Twenty-seven words were taught, three to three. In the end, the overall assessment was carried out again. Participants had different repertoires in relation to reading and writing skills, however, both increased the number of correct words read. Participant Patrick presented initial reading and writing repertories, also showed advances in writing. The assessment, at the beginning, is very important to indicate an adequate intervention
Keywords: reading; writing; individualized teaching; intellectual disabilities